Change in Religious Understanding and Language Shift of the Recitations of the Quran and Hadith in the Perspective of Islamic Jurisprudence - Ushalli, Eskarni; Salma; Hayati, Naila; Yuherlis, Neni; Kirin, Arwansyah (International Journal of Science and Society, 2024)
This writing aims to analyze the occurrence of changes in the understanding of the community and the shift in language of some recitations of the Quran and Hadith from the perspective of Islamic jurisprudence (fiqh). Understanding religion cannot be separated from the issue of language shift because the fundamental sources of Islamic teachings are the Quran and Hadith, both of which are in Arabic. The translation of verses from the Quran and Hadith into the Indonesian language is not without uncertainties. For example, the change in understanding of the word "telapak tangan" (palm of the hand) as a translation of the Arabic term "kaff," which excludes the back part of the palm, leading to difficulties in practice. This study is a literature review, and data collection and analysis were conducted using this method. Changes in the community's understanding of these words can be observed in the everyday practices of the community (observation). The results of the study indicate that one of the changes in the community's understanding is the shift from the term "kaff" to "telapak tangan." Its influence can be seen in the understanding and application of the boundaries of the female aurah (parts to be covered) and the attire during ihram. Based on Hadith, most people consider the boundaries of a woman's aurah to be everything except the face and both palms. In fiqh, it is mentioned that a woman in ihram is prohibited from covering her face and both palms. This understanding and practice differ from what is intended in the Hadith and fiqh texts.